Psycho-social factors influencing negative body image in women - ПОРТНЯГІНА, Марія (Київський національний університет імені Тараса Шевченка, 2025)
Background. The development of body image is a complex process shaped by biological, psychological, and socio-cultural factors. In modern society, beauty standards promoted by the media, social networks, and the fashion industry greatly influence women's perceptions of their bodies. High levels of self-criticism and the pursuit of an ideal imposed by culture can lead to negative outcomes such as lower self-esteem, psychological distress, and eating disorders. The study aims is to identify the key psycho-social factors that contribute to negative body image in women and to explore how body image relates to self-esteem, psychological well-being, and stress levels. Methods. The study included 61 women aged 24 to 59. The methodology involved administering several instruments: Body Image Questionnaire (O. Skugarevsky, S. Sivuha), "Psychological Well-being Scale" by C. Ryff, Multifactor Personality Research Method (16 PF) by R. Cattell, Perceived Stress Scale (PSS-10); and a Self-assessment lifestyle questionnaire. Data processing was conducted using descriptive statistics, Spearman's correlation analysis (r), and regression analysis. Results. Findings showed that overall satisfaction with body image among participants was moderate. However, 26% of women displayed tendencies toward a negative body image. Correlation analysis indicated a positive relationship between body image and psychological well-being (r=0.225; p<0.05). Higher stress levels were associated with poorer body image (r=-0.242; p<0.05), while self-esteem showed a strong positive link (r=0.414; p<0.01). Regression analysis revealed that self-esteem is the primary factor affecting body image (est=1.306; p<0.01), whereas increased stress levels serve as a negative predictor (est=-0.231; p<0.05). Additionally, value orientations were significant: physical (r=0.334; p<0.01) and intellectual (r=0.291; p<0.01) values correlated positively with body image. Conversely, perceiving one's lifestyle as "imperfect" was inversely related (r=-0.408; p<0.01). Conclusions. The findings confirm that negative body image in women results from various psycho-social factors. The most influential include self-esteem, stress levels, value systems, and subjective perceptions of lifestyle. Increased anxiety, emotional instability, and unrealistic beauty standards worsen body image. Future research should involve larger samples and the conduction of a comparative analysis among different age groups and genders.

Вступ. Соціокультурний контекст сучасного суспільства сприяє поширенню негативного сприйняття власного тіла у жінок. Ідеї ідеалізованих стандартів краси, що пропагуються засобами масової інформації та соціальними медіа, створюють додатковий психологічний тиск і можуть призводити до низки негативних наслідків, зокрема зниження самооцінки та появи емоційних розладів. Методи. У дослідженні взяли участь 61 жінка віком від 24 до 59 років. Застосовувалися: опитувальник образу власного тіла (О. Скугаревський, С. Сивуха), "Шкала психологічного благополуччя" К. Ріфф, методика багатофакторного дослідження особистості (16 PF) Р. Кеттелла, шкала сприйманого стресу (PSS-10), а також авторська анкета оцінки свого способу життя. Отримані дані оброблено методами описової статистики, кореляційного (r-Спірмена) та регресійного аналізу. Результати. Встановлено, що в цілому учасниці мають помірний рівень задоволеності власним тілом; проте 26 % опитаних виявили схильність до негативного образу тіла. Позитивний кореляційний зв'язок між показниками образу тіла та психологічним благополуччям (r = 0,225; p < 0,05) свідчить про важливість самоприйняття для збереження психічного здоров'я. Регресійний аналіз показав, що самооцінка суттєво підвищує рівень образу тіла (est = 1,306; p < 0,01), тоді як підвищений стрес спричиняє зворотний ефект (est = –0,231; p < 0,05). Серед ціннісних орієнтацій найбільш суттєві кореляції зафіксовано між образом тіла та фізичними (r = 0,334; p < 0,01) й інтелектуальними (r = 0,291; p < 0,01) цінностями. Висновки. Результати підтверджують комплексний вплив психо-соціальних чинників на формування негативного образу тіла у жінок. Рольових чинників декілька: самооцінка, рівень стресу, ціннісні пріоритети та уявлення щодо "правильного способу життя". Подальші дослідження мають охоплювати розширені вибірки та порівнювати жіночу вибірку з чоловічою. Це дозволить краще зрозуміти, як диференційовано впливають вікові й гендерні аспекти на формування образу тіла.
Психосоціальні чинники формування негативного сприйняття образу тіла у жінок
Keywords: body image; women; psychological well-being; stress; self-esteem; value orientations; lifestyle; образ тіла; жінки; психологічне благополуччя; стрес; самооцінка; ціннісні орієнтації; спосіб життя